1999
DOI: 10.2337/diacare.22.12.1956
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits, body weight, and insulin misuse. A longitudinal study of teenagers and young adults with type 1 diabetes.

Abstract: An increase in BMI from adolescence to adulthood was associated with higher levels of concern over shape and weight and more intense dietary restraint, especially among females. Overt eating disorders were no more prevalent in these patients than in the general population, but milder forms of disordered eating were common and had implications for diabetes management. Insulin omission for weight control was frequent among females and may contribute to poor glycemic control and to risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
187
3
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(206 citation statements)
references
References 0 publications
9
187
3
7
Order By: Relevance
“…This, in turn, may impair treatment adherence and impede therapy intensification, with consequent failure to achieve glycaemic goals 1, 2. Weight gain is associated with an increased risk of coronary heart and cardiovascular disease in people with diabetes 3, 4, a troubling prospect given that 80–90% of people with T2D are already overweight before insulin replacement 5.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, may impair treatment adherence and impede therapy intensification, with consequent failure to achieve glycaemic goals 1, 2. Weight gain is associated with an increased risk of coronary heart and cardiovascular disease in people with diabetes 3, 4, a troubling prospect given that 80–90% of people with T2D are already overweight before insulin replacement 5.…”
Section: Introductionmentioning
confidence: 99%
“…Rydall et al (8) found that DEB at the study baseline among a cohort of adolescent girls with type 1 diabetes predicted a tripled risk of retinopathy 4 years later. In a third study, Bryden et al (13) assessed a group of individuals with type 1 diabetes in adolescence and then again in early adulthood. They found that rates of overweight, concern over weight and shape, and heightened dietary restraint all increased from adolescence to adulthood.…”
mentioning
confidence: 99%
“…[24][25][26] Observando as diretrizes diagnósticas da CID 10 para BN, o item B descreve comportamentos para compensar as conseqüências da ingestão alimentar altamente calórica e faz uma referência a pacientes diabéti-cos: "quando a bulimia ocorre em pacientes diabéticos, eles podem escolher negligenciar seu tratamento insulínico". Herpertz et al 12 mostraram, numa amostra de 663 pacientes diabéticos dos tipos 1 e 2, a prevalência em comorbidade e distribuição dos três principais TA: a anorexia nervosa, a bulimia nervosa e o transtorno da compulsão alimentar periódica.…”
Section: 5-10unclassified